2005
DOI: 10.1128/mcb.25.17.7645-7656.2005
|View full text |Cite
|
Sign up to set email alerts
|

FoxO1a-Cyclic GMP-Dependent Kinase I Interactions Orchestrate Myoblast Fusion

Abstract: The regulatory circuits that orchestrate mammalian myoblast cell fusion during myogenesis are poorly understood. The transcriptional activity of FoxO1a directly regulates this process, yet the molecular mechanisms governing FoxO1a activity during muscle cell differentiation remain unknown. Here we show an autoregulatory loop in which FoxO1a directly activates transcription of the cyclic GMP-dependent protein kinase I (cGKI) gene and where the ensuing cGKI activity phosphorylates FoxO1a and abolishes its DNA bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…The interaction of FKHR with cyclic GMP-dependent protein kinase I causes myoblast fusion by influencing the fusion rate (22). Despite these findings, conflicting results have been reported; normal myogenic differentiation is impaired by the forced expression of constitutively active or wild-type FKHR in skeletal muscle cells (57,58).…”
Section: Fkhr Negatively Regulates Mrtf-a/smad-dependentmentioning
confidence: 74%
See 2 more Smart Citations
“…The interaction of FKHR with cyclic GMP-dependent protein kinase I causes myoblast fusion by influencing the fusion rate (22). Despite these findings, conflicting results have been reported; normal myogenic differentiation is impaired by the forced expression of constitutively active or wild-type FKHR in skeletal muscle cells (57,58).…”
Section: Fkhr Negatively Regulates Mrtf-a/smad-dependentmentioning
confidence: 74%
“…In various other cell types, FKHR that is phosphorylated by Akt, but not by ROCK, is also exported from the nucleus, leading to the inhibition of FKHR-mediated transcription (23). However, the target partners of FKHR and its function in myogenic differentiation remain unknown, except for a Foxo1a-cyclic GMP-dependent kinase I interaction (22).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The cGK1-induced phosphorylation seems to be specific for FOXO1 because the cluster of serine residues preceding the helix H1 is unique to FOXO1, and the residue Ser184 is absent in FOXO4 sequence (Figure 3c). Phosphorylation of FOXO1 by cGK1 efficiently inhibits its DNA-binding activity, in agreement with the fact that both these regions make polar and van der Waals interactions with DNA backbone, and the introduction of negatively charged phosphate groups would be expected to disrupt these contacts (Bois et al, 2005;Tsai et al, 2006Tsai et al, , 2007.…”
Section: Phosphorylation By Other Kinasesmentioning
confidence: 77%
“…Recently, it has been shown that the cyclic GMPdependent kinase-1 (cGK1) regulates FOXO1 activity during muscle cell fusion (Bois et al, 2005). FOXO1 directly activates cGK1 transcription and cGK1 then in turn harnesses FOXO1 activity by phosphorylating cluster of serine residue located upstream of the first helix H1 (Ser152-155 of FOXO1) and Ser184 in the N-terminal part of helix H2 (Figures 3c and 7).…”
Section: Phosphorylation By Other Kinasesmentioning
confidence: 99%